Theoretical elaboration : Persepolis: a synoptic elaboration of the story’s adaptation as graphic novel and animated film - Ata Vahedian Javaheri (Hochschule für Angewandte Wissenschaften Hamburg, 2024)
This thesis deals with the process of adapting Persepolis by Marjane Satrapi (2003) as a graphic novel into a two-dimensional animation film. Additionally, this thesis concentrates on substantive changes that Satrapi, as writer and co-director of Persepolis, had to make to realize the modification of the story. Furthermore, this elaboration examines the role of visual effects and sound design in the animation film and its influence on the audience’s perception.